Academic Reading Difficulties in Higher Education - Anwar, Indry Widyasti; Sailuddin, Sartika Putri (Universitas Pendidikan Mandalika, 2022)
Academic reading is one of the challenges commonly faced by university students especially EFL learners. This study aims to identify academic reading difficulties in higher education focusing on Indonesian university students. It used mixed-method by collecting quantitative data from close-ended questionnaires and qualitative data from one open-ended question. In this study, 60 students were asked to rate the reading aspects listed in the questionnaires based on its level of difficulty and provide commentaries as well as possible additional aspect. The statistic results showed that overall students considered academic reading easy (M=2.445, SD=0.568). Reading carefully to understand the text was found as the aspect with the least difficulty (M=2.16, SD= 0.963) and working out the meaning of difficult words was identified as the most difficult one (M=2.75, SD=1.235). These statistics are supported by the qualitative finding whereas 43% students having problems translating and understanding difficult and formal words.